Evaluating the Effectiveness of Task Delegation from Registered Nurses to Nursing Technicians in Enhancing Patient Satisfaction and Workflow Efficiency: A Cross-Sectional Study in KSA - Norah Ayad Surur Almutairi; Naif Sayah E Aldahmashi; Sulaiman Hamad M Alsaif; Mohammad Sahen Q Alanazi; Nouf Nashi M ALhwaiyani; Nawal Hanif Dahi Alanazi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Task delegation from registered nurses to nursing technicians has emerged as a strategy to optimize healthcare delivery and improve patient outcomes. This study aimed to evaluate the effectiveness of task delegation in enhancing patient satisfaction and workflow efficiency in healthcare settings in the Kingdom of Saudi Arabia (KSA). Methods: A cross-sectional study was conducted in selected hospitals in KSA. A total of 500 patients and 200 healthcare professionals (100 registered nurses and 100 nursing technicians) were recruited using stratified random sampling. Data were collected using structured questionnaires assessing patient satisfaction, workflow efficiency, and perceptions of task delegation. Descriptive and inferential statistics were used for data analysis. Results: The majority of patients (85%) reported high levels of satisfaction with the care provided by nursing technicians. Registered nurses and nursing technicians perceived task delegation as an effective strategy for improving workflow efficiency (90% and 88%, respectively). Task delegation was associated with reduced workload for registered nurses (p < 0.001) and increased job satisfaction among nursing technicians (p < 0.01). Challenges identified included the need for clear communication and adequate training for nursing technicians. Conclusion: Task delegation from registered nurses to nursing technicians appears to be an effective approach for enhancing patient satisfaction and workflow efficiency in healthcare settings in KSA. The findings highlight the importance of clear guidelines, effective communication, and appropriate training for successful task delegation implementation. Future research should explore the long-term impact of task delegation on patient outcomes and healthcare system performance.